PENGARUH IMPLEMENTASI KEBIJAKAN AKUNTANSI BERBASIS AKRUAL DAN KOMPETENSI SUMBER DAYA MANUSIA TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi pada Pemerintah Daerah Kabupaten Morowali Utara) - Helda Nelvia; Andi Kusumawati; Retno Fitrianti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2023)
This study aims to analyze the impact of implementation of accrual-based accounting policies and human resources competency to the quality of Morowali Utara local government’s financial statement. This research uses quantitative analysis method and using primary data through questionnaire. Respondent of this study were finance departments of 36 local government’s office of Kabupaten Morowali Utara. The variables in this study are the implementation of accrual-based accounting policies and human resource competencies as independent variables and the quality of local government financial reports as the dependent variable. Data analysis used statistical methods with multiple regression analysis. The results of the study indicate that the implementation of accrual-based accounting policies has a positive effect on the quality of local government financial reports. It means that if the financial statements is more in line with accrual-based accounting policies, the local government financial reports will be better. On the other hand, human resource competence has a positive effect on the quality of local government financial reports. This indicates that the higher the competence of human resources, the better it is in producing quality local government financial reports.